Recent Advances in Molecular Biology of Human Bocavirus 1 and Its Applications - Shao, Liting; Shen, Weiran; Wang, Shengqi; Qiu, Jianming (Frontiers in Microbiology, 2021)
Human bocavirus 1 (HBoV1) was discovered in human nasopharyngeal specimens in 2005. It is an autonomous human parvovirus and causes acute respiratory tract infections in young children. HBoV1 infects well differentiated or polarized human airway epithelial cells in vitro. Unique among all parvoviruses, HBoV1 expresses 6 nonstructural proteins, NS1, NS1-70, NS2, NS3, NS4, and NP1, and a viral noncoding RNA (BocaSR), and three structural proteins VP1, VP2, and VP3. The BocaSR is the first identified RNA polymerase III (Pol III) transcribed viral noncoding RNA in small DNA viruses. It plays an important role in regulation of viral gene expression and a direct role in viral DNA replication in the nucleus. HBoV1 genome replication in the polarized/nondividing airway epithelial cells depends on the DNA damage and DNA repair pathways and involves error-free Y-family DNA repair DNA polymerase (Pol) η and Pol κ. Importantly, HBoV1 is a helper virus for the replication of dependoparvovirus, adeno-associated virus (AAV), in polarized human airway epithelial cells, and HBoV1 gene products support wild-type AAV replication and recombinant AAV (rAAV) production in human embryonic kidney (HEK) 293 cells. More importantly, the HBoV1 capsid is able to pseudopackage an rAAV2 or rHBoV1 genome, producing the rAAV2/HBoV1 or rHBoV1 vector. The HBoV1 capsid based rAAV vector has a high tropism for human airway epithelia. A deeper understanding in HBoV1 replication and gene expression will help find a better way to produce the rAAV vector and to increase the efficacy of gene delivery using the rAAV2/HBoV1 or rHBoV1 vector, in particular, to human airways. This review summarizes the recent advances in gene expression and replication of HBoV1, as well as the use of HBoV1 as a parvoviral vector for gene delivery.